Management of Student Study Time Post-Pandemic Toward Culture Shock in Indonesia - Yuserizal Bustami; Eka Putra; Muhamad Zainal Arifin (Ta'dib, 2023)
This article aims to reveal the management of student study time after the Covid-19 pandemic in dealing with culture shock in Indonesia. This article uses qualitative research method. This type of research is a case study, namely culture shock post covid-19 pandemic. Research problems in research are explained descriptively. The data collection technique that is with the library such scientific articles, books, and other sources relevant to the research topic. The data analysis technique uses a technique popularized by Miles & Huberman, which consists of condensation, data presentation, and drawing conclusions. This study found that students experienced various culture shocks due to changes in the learning process, namely from offline face-to-face to online virtual face-to-face. Culture Shock happened again for the second time when the Covid-19 pandemic was gone, so all activities, namely offline learning, returned to normal. Therefore, to reduce the effect of culture shock, it is necessary to have adaptations in managing study time management, meaning that building and restructuring good study time management is the primary key to surviving these situations and conditions.